Muslim Americans: Debating the Notions of American and Un-American - Kabir, Nahid Afrose (© 2016 Taylor and Francis Inc., 2019)
This book was published by Taylor and Francis Inc., 2016. The publisher's website is at: https://www.taylorfrancis.com/books/9781315517254